2006
DOI: 10.1122/1.2188528
|View full text |Cite
|
Sign up to set email alerts
|

Local determination of the constitutive law of a dense suspension of noncolloidal particles through magnetic resonance imaging

Abstract: SynopsisWe investigate the flowing behavior of dense suspensions of non-colloidal particles, by coupling macroscopic rheometric experiments and local velocity and concentration measurements through MRI techniques. We find that the flow is localized at low velocities, and that the material is inhomogeneous; the local laws inferred from macroscopic rheometric observations must then be reinterpreted in the light of these local observations. We show that the short time response to a velocity step allows to charact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

30
268
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(303 citation statements)
references
References 77 publications
(157 reference statements)
30
268
4
1
Order By: Relevance
“…Experimental studies have confirmed that suspension viscosity ⌘ s increases with φ and diverges as φ approaches a maximal fraction φ m about 0.6 (Ovarlez et al 2006). Despite some differences among the various experimental results, the relation between viscosity and particle volume fraction is now reasonably well documented (Stickel & Powell 2005).…”
Section: Introductionmentioning
confidence: 52%
“…Experimental studies have confirmed that suspension viscosity ⌘ s increases with φ and diverges as φ approaches a maximal fraction φ m about 0.6 (Ovarlez et al 2006). Despite some differences among the various experimental results, the relation between viscosity and particle volume fraction is now reasonably well documented (Stickel & Powell 2005).…”
Section: Introductionmentioning
confidence: 52%
“…week ending 11 JANUARY 2008 0031-9007=08=100(1)=018301 (4) 018301-1 © 2008 The American Physical Society (MRI) rheometer from which we directly get the local velocity distribution in a Couette geometry with a gap of 1.85 cm [14]. We investigated the stationary flows for inner cylinder rotational velocity ranging between 0.2 and 10 rpm, corresponding to overall shear rates between 0.04 and 2:35 s ÿ1 .…”
mentioning
confidence: 99%
“…In most cases, these data have been obtained from macroscopic measurements (e.g., using rheometers), assuming that the bulk behaves as a homogeneous fluid, however there is accumulating evidence that this procedure leads to miscalculations of the bulk behavior. 19,20 The current trend is to infer rheological properties by local measurements. Flow visualization has made it possible to derive the rheological properties directly by measuring the local velocity and particle concentrations.…”
Section: Introductionmentioning
confidence: 99%